Counter-radicalism and Moderate Muslim in Jember - M. Khusna Amal (Al-Ulum, 2016)
This paper marks an attempt to understand and explain the cultural movement of the Nahdlatul Ulama (NU) and Muhammadiyah -two moderate Islamic organization with the largest mass in Indonesia - in countering the penetration of religious radicalism in Jember --one district in East Java. Despite using a different platform and approach, namely Islam of Archipelago and Islam Progressive, but the two organizations have the same prophetic political mission to fight all forms of radicalism in the name of religion. This paper argues that both the organization itself, it is still as a progressive pillar of Indonesian civil Islam who are concerned in fighting the agenda of tolerance, pluralism and democracy. Both also always positioned itself as an anti-thesis and always take opposition to radicalism forces. However, religious radicalism is a serious threaten especially to fight the agenda of diversity and peaceful coexistence of religious differences. So far, this paper intends to elaborate progressive ideas among moderate Muslims -NU and Muhammadiyah-- in consolidating themselves to stem the flow of radicalism.